A Meta-Analysis of the Association Between Radiation Therapy and Survival for Surgically Resected Soft-Tissue Sarcoma. (April 2018) - Qu, Xuanlu; Lubitz, Carrie C.; Rickard, Jennifer; Bergeron, Stephane G.; Wasif, Nabil
Abstract : Objectives: Radiotherapy for soft-tissue sarcoma (STS) has been shown to reduce local recurrence, but without clear improvement in survival. We conducted a meta-analysis to study the association between radiotherapy and survival in patients undergoing surgery for STS. Methods: A systematic review was conducted from PubMed, EMBASE, Web of Science, and Cochrane databases. Our population of interest consisted of adults with primary extremity, chest wall, trunk, or back STS. Our metameters were either an odds or hazard ratio for mortality. A bias score was generated for each study based on margin status and grade. Results: Of 1044 studies, 30 met inclusion criteria for final analysis. The pooled odds ratio in patients receiving radiation was 0.94 (95% confidence interval [CI], 0.78-1.14). The pooled estimate of the hazards ratio in patients receiving radiation was 0.87 (95% CI, 0.73-1.03) overall and 0.65 (95% CI, 0.52-0.82) for studies judged to be at low risk of bias. Significant publication bias was not seen. Conclusions: High-quality studies reporting adjusted hazard ratios are associated with improved survival in patients receiving radiotherapy for STS. Studies in which odds ratios are calculated from event data and those that do not report adjusted outcomes do not show the same association, likely due to confounding by indication. Abstract : Supplemental Digital Content is available in the text.